2014
DOI: 10.1155/2014/105214
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Ameliorates Early Diabetic Nephropathy in Streptozotocin-Induced Diabetic Rats

Abstract: Diabetic nephropathy results in end-stage renal disease. On the other hand, carvedilol has been reported to have various pharmacological properties. The aim of this study therefore is to evaluate the possible protective effect of carvedilol on streptozotocin-induced early diabetic nephropathy and various mechanisms underlie this effect in rats. Single i.p. injection of streptozotocin (65 mg/kg) was administered to induce early diabetic nephropathy in Wistar rats. Oral administration of carvedilol at a dose lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
(32 reference statements)
1
16
0
3
Order By: Relevance
“…Studies have shown that carvedilol has markedly improved cardiac performance and reduced mortality in humans [21,22]. Morsy et al [9] reported that carvedilol can protect STZ-induced early diabetic nephropathy in rats via antioxidant as well as anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that carvedilol has markedly improved cardiac performance and reduced mortality in humans [21,22]. Morsy et al [9] reported that carvedilol can protect STZ-induced early diabetic nephropathy in rats via antioxidant as well as anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…The diabetic rats were treated with carvedilol (10 mg/kg/day p.o. [9]; Roche, Indianapolis, IN, USA) or vehicle for 16 weeks. All the rats were provided with water and food ad libitum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that carvedilol ameliorates renal dysfunction even in streptozotocin‐diabetic animals with a concomitant reduction in oxidative stress . In these studies, thiobarbituric acid‐reactive substances, malondialdehyde, glutathione and the nitrite/nitrate ratio were evaluated as markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Од-новременно у крыс с СД по сравнению с нелечены-ми животными снижается уровень сывороточного креатинина, возрастает почти в 3 раза клиренс креа-тинина и более чем в 2 раза снижается отношение альбумин/креатинин мочи. По данным электронной микроскопии карведилол практически полностью восстанавливает к этому времени толщину гломеру-лярной базальной мембраны и препятствует отщеп-лению ножек подоцитов, сохраняя их морфологиче-скую структуру [26].…”
Section: доклиническая оценка нефропротекторных свойств карведилолаunclassified